DIP-COATING SENYAWA KALSIUM FOSFAT DARI BATU KAPUR BUKIT TUI MELALUI METODE SOL-GEL - Jamarun, Novesar; Anggresani, Lia; Arief, Syukri (Universitas Andalas, 2011)
ABSTRACT Preparation of Dip-Coating Calcium Phosphate via sol-gel method using natural limestone Bukit Tui as calcium precursors and diammonium hydrogen phosphate as phosphorus precursors with sol-gel process has been investigated. Ethanol was used as solvent and DEA (diethanolamine) was used stabilizing agent. The powder were prepared by calcinated the sol at 950 oC. The products were characterized by Fourier Transform Infra Red, X-Ray Diffraction and Scanning Electron Microscopy. FTIR results showed that the vibration form was PO43-, P2O74-, O-H and CO2. XRD patterns of powder with various Ca/P mol ratio showed that the product of calcium phosphate was Ca2P2O7 and also found the hydroxyapatite Ca10(PO4)6(OH)2 in Ca/P mol ratio 1,7. SEM images of powder calcium phosphate revealed that their morphology were spheric and homogen. The coating process was done at glass substrate with coating speed 20 cm/min by calcinations at 400 oC. XRD patterns of thin layer showed that the product was Ca2P2O7 and SEM images of thin layer revealed that their morphology were bulk. Keywords: Natural limestone, calcium phosphate, hydroxyapatite, sol-gel, dip-coating